Folded conical helix antenna. - Dobbins, J.A.
A novel conical monopole antenna composed of multiple spiral wires for the HF to VHF frequency bands is presented. The antenna exhibits broad bandwidth and good efficiency in an electrically small package. Broadbanding and impedance matching techniques used during the design process of this antenna are described. Measured data from a VHF version of this antenna is shown. The performance of this antenna is then compared to the performance of other electrically small antennas
Keywords: HF frequency band; VHF frequency band; Bandwidth; Broadbanding techniques; Efficiency; Electrically small antennas; Electrically small package; Electrically small wire antenna; Folded conical helix antenna; Impedance matching